Implementasi Extreme Programming Pada Perancangan Sistem Informasi Inventory Berbasis Web Terintegrasi Whatsapp Gateway Pada NB-Store - Muhamad Syahruli; Dimas Abisono Punkastyo (CV. Multi Kreasi Media, 2024)
The use of information and communication technology is now growing in various fields and circles. One of them is a trading company. Information and communication technology is utilized by trading companies in managing merchandise, transacting goods and so on which can help facilitate and simplify the work in that one company or organization. NB-STORE accepts consumers who buy various types of fashion. However, when the transaction process runs slowly and sometimes there are errors in the difference between the stock of goods stored and the stock of goods that are recorded. Because in the process of processing inventory data, it is still done manually by the admin, namely for data collection of incoming and outgoing goods, inventory data collection is only recorded in the book and then transferred to Microsoft Excel. So that from these problems there are often errors in calculating goods, difficulties in recording, making reports on incoming goods, outgoing goods, which are in accordance with receipts or travel documents from customers or suppliers and the difficulty in finding the required item data because of the high cost of many files. it is time for NB-STORE to migrate using applications in data management such as data processing of incoming and outgoing goods and stock of goods with applications that are more efficient and accurate. The problem with the current running system is to record reports manually, namely to record all existing inventory with written reports written directly by employees and then recalculated and adjusted to existing stock. With the existence of an inventory information system that has been designed, it is expected that it will make it easier to carry out incoming and outgoing goods so that the management of inventory reports can be carried out by users properly.